Depression among underserved rural and urban caregivers of Latinas with breast cancer. Issue 3 (3rd April 2023) - Cordova-Marks, Felina M.; Valencia, Celina; Badger, Terry A.; Segrin, Chris; Sikorskii, Alla
ABSTRACT: Among Latino/as, informal caregiving duties are often deemed a family responsibility. Understanding psychological outcomes tied to caregivers of Latina breast cancer survivors is important to identify the impacts of cancer. Secondary analysis of baseline data collected in a randomized clinical trial (RCT) from 230 Latina breast cancer survivor–caregiver dyads. Characteristics of caregivers residing in rural/underserved and urban areas were compared using t- or chi-square tests. General linear models were used to analyze depressive symptoms in relation to residence, survivor–caregiver relationship, acculturation, obligation, reciprocity, and comorbidities. Urban residence was significantly associated with higher levels of depression controlling for survivor–caregiver relationship acculturation, obligation, reciprocity, and comorbidities. Mother caregivers had significantly higher levels of depression than other caregivers. Depression among Latino/a caregiver's providing care to an adult child is an important consideration as Latino/as are less likely to seek out/have access to mental health services than other groups.